Analysis of Anodic Corrosion and Discharge Performance of Lithium Sulfur Air Battery in 10 mmol/L LiPF6 Electrolyte - ZHANG Xiao - bin (Cailiao Baohu, 2021)
In order to improve the discharge performance of lithium sulfur air battery anode in 3.5% NaCl electrolyte, the corrosion and discharge performance of lithium sulfur air battery anode were studied by adding 10 mmol/L LiPF6 into the electrolyte. Results showed that when 10 mmol/L LiPF6 was added into 3.5% NaCl solution, the anodic corrosion rate decreased obviously after 4 days, from 0.350 mg/(cm2·h) to 0.024 mg/(cm2·h), indicating that the corrosion resistance of the anode was significantly enhanced. After the addition of LiPF6, the anode shifted a higher corrosion potential, and the slope of anode polarization curve remained basically constant. The anodic corrosion current density decreased from 44.26 μA/cm2 to 20.08 μA/cm2 by adding LiPF6 into the solution, which significantly enhanced the corrosion resistance of the anode. LiPF6 significantly increased the discharge voltage from 0.55 V to 0.74 V at the current density of 14 mA/cm2. Therefore, LiPF6 significantly enhanced the electrode discharge activity and reduced the self - corrosion rate in the discharge reaction stage of lithium alloy. After the addition of LiPF6, Mg(OH)2 was mainly formed on the corrosion surface, with a small amount of Al(OH)3 and PbO2.